Peran Pemerintah Desa dalam Pemberdayaan Masyarakat Lokal di Desa Ujung Serdang Kecamatan Tanjung Morawa - Siburian, Yeremia Elkana Tua; Ivanna, Julia (Majalah Ilmiah METHODA, 2024)
The Ujung Serdang Village Government plays a crucial role in empowering the local community, focusing on economic development and cultural preservation. These initiatives aim to enhance welfare, economic independence, and local wisdom. However, challenges such as lack of community awareness and insufficient support from the central government persist. This study analyzes the village government's role through implemented programs and their impacts, using a descriptive qualitative method. The results are expected to provide insights into effective empowerment mechanisms and identify obstacles for future improvements.